Molecular taxonomy reveals an overlooked cryptic species of the tiger moth genus Murzinowatsonia Dubatolov (Lepidoptera, Arctiinae) from Sichuan, China. Issue 27 (18th July 2021) - Saldaitis, Aidas; Volynkin, Anton V.; Han, Hui Lin; Zahiri, Reza
ABSTRACT: One new Murzinowatsonia species, ( Murzinowatsonia amelija sp. nov.), is described from Sichuan, China. Morphological characteristics, DNA sequence data (barcode region and four nuclear protein-coding genes), divergence time estimation, and habitat preferences are provided for the new species along with a morphological comparison with Murzinowatsonia x-album (Oberthür, 1911) and genetic distances between the species. Our estimated divergence time showed that divergence of M. amelija and M. x-album from a common ancestor started during the Early Pleistocene ( 1.45 Mya). The relatively low divergences among haplotypes of two Murzinowatsonia species may suggest that these species originated recently during the Mid-Pleistocene (i.e. 0.126–0.781 Mya). The current number of valid species in the genus is two. http://www.zoobank.org/urn:lsid:zoobank.org:pub:E7B5ADCF-E862-4784-8E30-89E11C0E3E81